THE MAIN DIFFICULTIES FOR VEGETARIANS TO BECOME VEGANS: A STUDY WITH BRAZILIAN CONSUMERS - Carolina Andrade Queiroz; Debora Fernanda Gonsalves Soliguetti; Sérgio Luiz do Amaral Moretti (Universidade do Estado do Rio de Janeiro, 2018)
Vegetarianism and veganism are much more than simple diets. They are a philosophy of life that, through eating, proposes questions and changes of attitudes about normally accepted standards. In spite of its importance, the theme has been neglected and publications available in Portuguese are rare. In order to fill this gap, this article seeks to investigate vegan activism and to understand the real motivations for adherence and, especially, the difficulties vegetarians face in becoming vegans. To meet this purpose, a survey was carried out with vegetarians and supporters. The bibliographical research has characterized the types of vegetarian diet and the main motivations for vegans to maintain thisway of life, considering materials, such as articles, reports, books and documentaries that defend animal rights, sentience and respect for species. The results of the research indicate that there is a desire on the part of the public related to vegetarianism/veganism to broaden their diet. The barriers to this decision are indicated as: high prices, restricted distribution and lack of product and brand options. DOI: 10.12957/demetra.2018.33210